Does the European Central Bank speak differently when in parliament? - Nicolò Fraccaroli; Alessandro Giovannini; Jean-François Jamet; Eric Persson (European Central Bank (ECB), 2022)
Parliamentary hearings are a fundamental tool to hold independent central banks accountable. However, it is not clear what type of information central banks provide when they communicate with parliaments compared to other existing information channels. In this article, we address this question by comparing the communication of the European Central Bank (ECB) in parliamentary hearings to its communication in the regular press conferences that follow monetary policy decisions. Using text analysis on the ECB President's introductory statements in parliamentary hearings and press conferences from 1998 to 2021, we show that the ECB uses parliamentary hearings to discuss topics that are less covered in press conferences. We also find that the ECB's policy stance in the hearings tends to reflect the stance in press conferences, and that the degree of language complexity is similar in the two fora. These findings support the view that the ECB mainly uses parliamentary hearings to further explain policy decisions first presented at press conferences but also to put them in a broader context.
Keywords: E02; E52; E58; 330; Central Bank Accountability; Central Bank Communication